Hannah Arendt, Stimme im Kanon der abendländischen politischen Ideengeschichte: Hannah Arendt, Stimme im Kanon der abendländischen politischen Ideengeschichte - Ludz, Ursula (HannahArendt.net, 2022)
Dana Villa, Arendt, London-New York: Routledge, 2021, 416 S. Paperback £ 19.99. eBook £ 16.99.